Synthesis of TiO2/Ga2O3@MIL-125(Ti) as a potential catalyst for photodegradation of methylene blue and oxygen evolution reaction. Issue 6 (3rd June 2022) - Mumtaz, Uzma; Fiaz, Muhammad; Athar, Muhammad
Abstract: Due to rapid increased in water toxicity by organic dyes and to fulfill the energy crises, development of efficient photocatalyst has attracted a lot of research attention. Therefore, in this work, an immensely effective photocatalyst TiO2 /Ga2 O3 @MIL-125(Ti) has been developed via incorporation of TiO2 /Ga2 O3 nanocomposite into MIL-125(Ti) by using refluxed method. Powdered XRD, SEM and UV-VIS spectroscopy methods are used for the accurate characterization of synthesized samples. These techniques reveal that all the synthesized materials have been successfully formed. It also shows that heterojunctions have been successfully developed via incorporation of pre-synthesized materials into host MOF. All the synthesized samples are used to study photodegradation efficiency of methylene blue and photoelectrochemical oxygen evolution reaction via water splitting. It has been observed that TiO2 /Ga2 O3 @MIL-125(Ti) has been emerged as highly effective catalyst toward photodegradation of methylene blue as well as oxygen evolution reaction. This high efficiency is due to collaborative effect and heterojunction formation of TiO2 /Ga2 O3 nanocomposites with central metallic cluster of MIL-125(Ti), which increases the charge separation, reduces the electron-hole pair recombination and enhances the absorption of visible light. TiO2 /Ga2 O3 @MIL-125(Ti) has been photodegraded methylene blue upto 40.29% and delivers 100 mAcm −2 at just 318 mV overpotential. Graphical Abstract: UF0001